IMPLEMENTATION ANALYSIS OF THE NO SMOKING AREA POLICY: BRIDGING THE GAP BETWEEN NORMATIVE GOALS AND FIELD REALITIES IN URBAN AND RURAL CONTEXTS - Iqbal, Wira; Miko, Alfan; Nurti, Yevita; Koeswara, Hendri (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2025)
The No Smoking Area (KTR) policy is one of the efforts to control the health effects of exposure to cigarette smoke. Its implementation shows a gap between normative goals and reality in the field. Implementation disparities between urban and rural areas indicate that the local context plays an important role in the effectiveness of the policy. This study aims to evaluate the effectiveness of KTR implementation in Indonesia through a Systematic Literature Review approach with a focus on comparison between urban and rural contexts. The review procedure was conducted based on the PRISMA protocol by screening scientific literature from the Scopus database. KTR implementation faces multidimensional challenges ranging from weak cross-sectoral supervision and coordination, low public awareness, and social resistance to regulations. Compliance is higher in health facilities, but still low in other public spaces, especially in areas with limited institutional capacity. This paper emphasizes the importance of a policy implementation approach that is adaptive to local characteristics and actively involves community actors. This paper also offers practical implications for strengthening KTR policy governance in a more participatory and sustainable manner to support public health development goals.